Greek biology students’ knowledge and perceptions of Natura 2000 protected areas - OIKONOMOU, ANTHI; STASINAKIS, PANAGIOTIS K.; MAVRIKAKI, EVANGELIA; PAFILIS, PANAYIOTIS (Mediterranean Marine Science, 2025)
Education is an important component to achieve biodiversity conservation. Given the need to increase environmental awareness and literacy towards more effective biodiversity conservation and more participatory management of protected areas, this paper aims to investigate the level of knowledge and perceptions of Biology students in Greece on Natura 2000 protected areas. The research was conducted using a standardized questionnaire, administered to 434 students from five biology departments. The students’ knowledge score was notably low and the department of their study did not differentiate the level of knowledge. In contrast, students in more advanced academic years or interested in Ecology, Zoology or Botany demonstrated a higher knowledge score than participants interested in other scientific disciplines. The majority of the students agreed with the establishment of a protected area in their place of residence. In terms of Natura 2000 management, NGOs, independent authorities and governmental organizations were more favored to the private sector. Regarding Natura 2000 site financing, the payment of users in specific areas and the purchase of local products are preferred. To integrate biodiversity conservation concepts in ecology study programmes and textbooks, the participation of experts from multiple scientific fields and the integration of a diverse array of teaching methods and tools are imperative.